Biofiltration System for Purification of Composting Waste Gases (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The biofiltration technique for the purification of polluted air from composting facility volatile compounds was studied. Two different biowaste composting techniques were compared with regard to emission of NH3 and H2S. The ammonia removal was observed in aerobic phase of active composting period, respectively H2S in anaerobic phase. Biofiltration process was realized in modified solid- state fermentation system (SSF). The biodegradation of volatile compounds was investigated in one and two stage systems with inert packing material and hemoautotrofic microorganisms designed DN-1 (Pseudomonas sp.), DN-2 (Nitrisomonas sp.), DN-3 (Nitrobacter sp.) and DN-13 (Sarcina sp.) and Thiopharus-3. The observed concentration of volatile H2S in composting reactor not exceeded 120 mg/m3 and the biofilter can be used to control this gas emission. Since NH3 is a toxic compaund for biofilter at a concentrations 400 mg/m3, multi- stage biofilter system is recommended to control the pollution in aerobic compost reactor.